Contemporary Academic Publishing: Democratization and Differentiation in Careers. (2nd November 2018) - Hermanowicz, Joseph C.; Clayton, Kristen A.
ABSTRACT: This study examined how publishing figures in the careers of academics as a means to study the social organization of higher education. Publishing is a means by which academics legitimate themselves. Yet previous work has demonstrated that most academics publish comparatively little. A classic literature in the sociology of science has used employing organization and career phase as chief devices by which to understand how academic fields are stratified. The study treated the field of sociology as a case by which to examine publication processes across cohorts of academics and stratified tiers of academic work. This article argues that a major transformation marks contemporary academic careers: Publication in science and scholarship is increasingly democratized. This article concludes with a discussion on three sets of macro conditions—massification, saturated labor markets, and neoliberalism—that may be understood for their democratizing effects on the career patterns of contemporary academics.